In Memoriam Paul Moedikdo (1927-2016) Pakar Kriminologi Yang Berpendirian Tegas Sebuah Nekrologi Oleh Jan Van Olden - Reksodiputro, Mardjono, Prof. (UI Scholars Hub, 2017)
Paul Moedikdo is just one of the many Indonesians who settled in the Netherlands because they were forced by circumstances resulting from the political upheaval in Indonesia in 1965 where there was an